Plin5 Bidirectionally Regulates Lipid Metabolism in Oxidative Tissues. (31st March 2022) - Zhang, Xinqing; Xu, Wu; Xu, Rui; Wang, Zhen; Zhang, Xinyan; Wang, Peng; Peng, Ke; Li, Meiling; Li, Jing; Tan, Yanfei; Wang, Xiong; Pei, Haifeng
Abstract : Cytoplasmic lipid droplets (LDs) can store neutral lipids as an energy source when needed and also regulate the key metabolic processes of intracellular lipid accumulation, which is associated with several metabolic diseases. The perilipins (Plins) are a family of proteins that associate with the surface of LDs. As a member of Plins superfamily, perilipin 5 (Plin5) coats LDs in cardiomyocytes, which is significantly related to reactive oxygen species (ROS) production originated from mitochondria in the heart, consequently determining the progression of diabetic cardiomyopathy. Plin5 may play a bidirectional function in lipid metabolism which is in a state of dynamic balance. In the basic state, Plin5 inhibited the binding of comparative gene identification-58 (CGI-58) to adipose triglyceride lipase (ATGL) by binding CGI-58, thus inhibiting lipolysis. However, when the body is under stress (such as cold, fasting, exercise, and other stimuli), protein kinase A (PKA) phosphorylates and activates Plin5, which then causes Plin5 to release the binding site of CGI-58 and ATGL, prompting CGI-58 to bind to ATGL and activate ATGL activity, thus accelerating the lipolysis process, revealing the indispensable role of Plin5 in lipid turnover. Here, the purpose of this review is to summarize the present understanding of the bidirectional regulation role of Plin5 in oxidative tissues and to reveal its potential role in diabetic cardiomyopathy protection.